Itm2a expression marks periosteal skeletal stem cells that contribute to bone fracture healing - Xing, Wenhui; Feng, Heng; Jiang, Bo; Gao, Bo; Liu, Jiping; Xie, Zaiqi; Zhang, Yazhuo; Hu, Xuye; Sun, Jun; Greenblatt, Matthew B.; Zhou, Bo O.; Zou, Weiguo (The Journal of Clinical Investigation, 2024)
The periosteum contains skeletal stem/progenitor cells that contribute to bone fracture healing. However, the in vivo identity of periosteal skeletal stem cells (P-SSCs) remains unclear, and membrane protein markers of P-SSCs that facilitate tissue engineering are needed. Here, we identified integral membrane protein 2A (Itm2a) enriched in SSCs using single-cell transcriptomics. Itm2a+ P-SSCs displayed clonal multipotency and self-renewal and sat at the apex of their differentiation hierarchy. Lineage-tracing experiments showed that Itm2a selectively labeled the periosteum and that Itm2a+ cells were preferentially located in the outer fibrous layer of the periosteum. The Itm2a+ cells rarely expressed CD34 or Osx, but expressed periosteal markers such as Ctsk, CD51, PDGFRA, Sca1, and Gli1. Itm2a+ P-SSCs contributed to osteoblasts, chondrocytes, and marrow stromal cells upon injury. Genetic lineage tracing using dual recombinases showed that Itm2a and Prrx1 lineage cells generated spatially separated subsets of chondrocytes and osteoblasts during fracture healing. Bone morphogenetic protein 2 (Bmp2) deficiency or ablation of Itm2a+ P-SSCs resulted in defects in fracture healing. ITM2A+ P-SSCs were also present in the human periosteum. Thus, our study identified a membrane protein marker that labels P-SSCs, providing an attractive target for drug and cellular therapy for skeletal disorders.